No correlation between multi‐locus heterozygosity and fitness in the common buzzard despite heterozygote advantage for plumage colour. (28th August 2013) - Boerner, M.; Hoffman, J. I.; Amos, W.; Chakarov, N.; Kruger, O.
Abstract: Correlations between heterozygosity and fitness are frequently found but rarely well understood. Fitness can be affected by single loci of large effect which correlate with neutral markers via linkage disequilibrium, or as a result of variation in genome‐wide heterozygosity following inbreeding. We explored these alternatives in the common buzzard, a raptor species in which three colour morphs differ in their lifetime reproductive success. Using 18 polymorphic microsatellite loci, we evaluated potential genetic differences among the morphs which may lead to subpopulation structuring and tested for correlations between three fitness‐related traits and heterozygosity, both genome wide and at each locus separately. Despite their assortative mating pattern, the buzzard morphs were found to be genetically undifferentiated. Multilocus heterozygosity was only found to be correlated with a single fitness‐related trait, infection with the blood parasite, Leucocytozoon buteonis, and this was via interactions with vole abundance and age. One locus also showed a significant relationship with blood parasite infection and ectoparasite infestation. The vicinity of this locus contains two genes, one of which is potentially implicated in the immune system of birds. We conclude that genome‐wide heterozygosity is unlikely to be a major determinant of parasite burden and body condition in the polymorphic common buzzard.